The Influence of Accountability, Transparency and Supervision on Budgeting Performance with the Concept of Value for Money in Village Owned Enterprises in Klaten Regency - Desi Anggraini; Sucahyo Heriningsih; Windyastuti Windyastuti (AIBPM Publisher, 2021)
This study determines the effect of accountability, transparency, and supervision on budget performance with the concept of value for money in village-owned enterprises in the Klaten district. This study uses primary data with a questionnaire data collection instrument distributed directly to respondents. The population in this study is all village-owned enterprises in the Klaten district. The sample in this study was 21 village-owned enterprises obtained from the sample collection method, namely purposive sampling, and received 44 respondents. Questionnaire data were tested using multiple linear regression analysis. The results showed that accountability did not affect budget performance with the concept of value for money. Transparency effects budget performance with the idea of value for money. And supervision affects budget performance with the idea of value for money.